2018
DOI: 10.31248/jbbd2017.044
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation and proximate analysis of varieties of some edible leafy vegetables in Northern Nigeria

Abstract: Vegetables are highly consumed in all the states across Northern Nigeria where they constitute a major source of nutritious food. However, their assessment as food, which is based on their chemical analysis, has not been adequately studied and documented in the areas. Standard procedures were used to determine the proximate and chemical composition of all vegetable species analysed. Atomic absorption and flame spectrophotometer test was used to determine the mineral composition. The results were compared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 9 publications
7
4
0
Order By: Relevance
“…Crude protein contents ranged between 7.80-10.91% in for vegetables. These percentages agreed with those reported by Oluwole et al [7] but were lower than those reported by Odoh et al [31] and Chatepa and Masamba [32] for some commonly consumed vegetables Africa. Thus, plant based proteins are reported to supply up to 12% body proteins [33].…”
Section: Proximate Compositions Of Four Vegetables Commonly Consumed ...supporting
confidence: 91%
See 4 more Smart Citations
“…Crude protein contents ranged between 7.80-10.91% in for vegetables. These percentages agreed with those reported by Oluwole et al [7] but were lower than those reported by Odoh et al [31] and Chatepa and Masamba [32] for some commonly consumed vegetables Africa. Thus, plant based proteins are reported to supply up to 12% body proteins [33].…”
Section: Proximate Compositions Of Four Vegetables Commonly Consumed ...supporting
confidence: 91%
“…However, carbohydrate contents in the four vegetables ranged from 67.51-77.63%. These values conform to the findings of Hussain et al [30] and Oluwole et al [7] but were above those documented by Odoh et al [31]. Carbohydrates are one of the essential energy sources in diet and as much as 60% may be provided [34].…”
Section: Proximate Compositions Of Four Vegetables Commonly Consumed ...supporting
confidence: 90%
See 3 more Smart Citations